PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE MAM (MAKE A MATCH) DENGAN STAD (STUDENT TEAM ACHIEVEMENT DIVISION) PADA MATERI SISTEM SARAF MANUSIA - Bunga Gustiana Napitupulu; Erlintan Sinaga; Juliana Lubis; Maria Butarbutar (Universitas Negeri Medan, 2019)
This research is aimed to know the difference of students’ learning score who were taught by using cooperative MaM (Make a Match) dan STAD (Student Team Achievement Division) model in neural system of human’s body material in grade XI MIA SMA Negeri 1 Hamparan Perak year of academic 2017/2018. This research is design as an experimental. The population of this research is 68 students, and the sample was taken by random sampling, which XI IPA 4 class (as MaM class) there are 34 students and XI IPA 2 class (as STAD class) there are 34 students. The data is collected by using multiple choice question test consist of 25 items. Based on the analysis requirements data, the average value of students’ learning score in MaM model at 77.06 with SD 9.66 and students’ learning score in STAD model at 81,41 with SD 8,46. The Result of hypothesis test by using t-test at significant level of 0.05, it concluded that there was the difference of students’ learning score by using cooperative learning MaM and STAD model in neural system of human’s body material in grade XI IPA SMA Negeri 1 Hamparan Perak academic year 2017/2018. Keywords : Students’ learning score, MaM model, STAD model.